The Urgency of Abou El Fadl's Hermeneutics in the Book "In the Name of God" - Wardhani, Nanda Kusuma; Zulfah, Evie Miftalia; A.J, Moh Iqbal Fachrullah; Humaira, Dirra Esya (Transformatif, 2023)
Hermeneutics is a branch of philosophy concerned with interpreting meaning. In Islamic religion, hermeneutics have something in common with interpretation. It is the presence of a text or message, the person delivering it, and the person who needs to understand it. This writing aims to expose Khaled M. Abou El Fadl's hermeneutics in his book On the Name of God, which arose from Khaled's disagreement with the misogynistic fatwa issued by UCLA. This research uses a qualitative approach with content analysis. In solving the problems related to the interpretation of the text, Khaled Abou el Fadl offers to negotiate hermeneutics. Hermeneutics negotiates the complex interactions between three: the author, the text, and the reader. This research indicates that the role of the writer, text, and reader is more important than in religious texts. Additionally, the reader interpreting the text must fulfill five conditions: honesty, sincerity, integrity, rationality, and self-control. This approach emphasizes the importance of understanding the social, cultural, historical, and linguistic contexts behind religious texts to interpret them correctly. Several points emphasize the importance of Khaled Abou El-Fadl's hermeneutics, namely contextuality, in-depth understanding, ethical and moral importance, responsive and relevant to the development of the times, the last being multidisciplinary use that combines knowledge of religion, history, philosophy, and social sciences.